Aesthetics on the street: rethinking the terms of engagement in public art practice - Gray, Brenden (My University, 2010)
Abstract: A theoretical and grounded study of dialogical art-making/drawing in informal, neighbourhood domains in order to reflect what social aesthetics and modalities of participation emerge through collaborative practices of drawing and speaking with residents of the Yeoville community Johannesburg. • Dialogical • Drawing • Informal • Social aesthetics • Collaboration • Community • Participation